Such is life on Toe Rag Lane - Nelson, Judy (Judy Uehlein) ([Westbury, Tasmania] : Judy Uehlein Nelson, 2020)
"It has taken me over a year to write a book about Westbury specifically about Mary Ann Street, once named Toe Rag Lane. My neighbour Gwen Boyer was born and raised in the house next door, once the home to Lieutenant Dexter, built in 1828. I live in the Military Barracks that once housed a Corporal and a Sergeant. This is the story about this quiet lane and about the Frosts, Gillams, Sturzakers, Leiths, Heathcotes, Reids, Brewards, Boyers and others who lived on this & adjoining streets. The Westbury Zoo and the Swamp will be looked at, both with their own stories to tell."--Author's webpage.
Spiral bound.
Includes bibliographical references (pages 163-164) and index.
Keywords: Streets -- Tasmania -- Westbury -- History; Dwellings -- Tasmania -- Westbury; Historic buildings -- Tasmania -- Westbury; Cottages -- Tasmania -- Westbury -- History; Pioneers -- Tasmania -- Westbury; Mary Ann Street (Westbury, Tas.) -- History; Westbury (Tas.) -- History; Westbury (Tas.) -- Buildings, structures, etc -- History; Australian; Biographies